Maternal Behavior Regarding Stunting Prevention Using Health Belief Model - Lailil Fatkuriyah; Ulfia Fitriani Nafista; Ainul Hidayati; Umi Sukowati (Universitas Tribhuwana Tunggadewi, 2026)
The national prevalence of stunting among children in Indonesia has yet to meet the WHO’s minimum target of below 20%. Furthermore, in Jember Regency, 34.9% of children were affected by stunting in 2023. Stunting not only leads to a shorter height compared to peers of the same age but also has both short-term and long-term effects that can deteriorate a child's health and even increase the risk of mortality. A mother's engagement in stunting prevention is affected by perceptions and beliefs, including perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, and self-efficacy. The aim of this research was to identify factors related to maternal behavior regarding prevention of stunting using the Health Belief Model approach. This study is an analytical observational research using a cross-sectional approach. It was conducted in Karengrejo Village, Jember Regency, involving 88 mothers of children under five. Participants were recruited through purposive sampling. The independent variables include: perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, and self-efficacy. The dependent variable is stunting prevention behavior. Data collection was conducted using the Health Belief Model questionnaire and the Stunting Prevention Behavior questionnaire. Data analysis was performed using the Spearman Rho statistical test with a significance level of 0.05. Statistical test results show that perceived susceptibility (p=0.011; r=0.273), perceived severity (p=0.018; r=0.254), and self-efficacy (p=0.004; r=0.310) have a significant relationship with maternal stunting prevention behavior. Strategies should be implemented to strengthen mothers' perceived susceptibility, perceived severity, and self-efficacy, encouraging greater involvement in stunting prevention through various programs, such as counseling, education, and home visits to increase mothers’ knowledge and skills related to appropriate feeding practices.